A Photochemical Microfluidic Reactor for Photosensitized [2+2] Cycloadditions - Bargum, Martin; Krell-Jørgensen, Mikkel; Nielsen, Martin; Qvortrup, Katrine; Laraia, Luca (Synlett, 2022)
Here we report a microfluidic system for photochemical cycloadditions fabricated using silicon micro processing technologies. The system was optimized to yield residence times of just a few minutes for a range of photochemical [2+2]-cycloaddition reactions facilitated using high power UV-LEDs at 375 nm and triplet photosensitizers, which removed the need for the low wavelengths typically required for these types of transformations. Adducts using different excitable olefins with different linear, carbocyclic, and heterocyclic coupling partners were explored to demonstrate the feasibility of performing photochemistry in microflow in an academic research environment. Finally, a reaction leading to a novel dihydrooxepin-2(3H)-one scaffold and a mechanistic proposal for its formation are reported.
Keywords: photochemistry; flow chemistry; cycloadditions